Advantage of high b value diffusion-weighted imaging for differentiation of common pediatric brain tumors in posterior fossa. Issue 128 (July 2020) - Takeishi, Yusuke; Takayasu, Takeshi; Kolakshyapati, Manish; Yonezawa, Ushio; Amatya, Vishwa Jeet; Takano, Motoki; Taguchi, Akira; Takeshima, Yukio; Sugiyama, Kazuhiko; Kurisu, Kaoru; Yamasaki, Fumiyuki
Highlights: Statistical inverse correlation at regular b-value based ADC and the cellularity. High b-value based ADC reflects the cellularity more accurately. The cellularity of pediatric posterior fossa tumors depends on pathological types. High b-value based ADC helps differentiation of pediatric posterior fossa tumors. Abstract: Purpose: The pediatric posterior fossa (PF) brain tumors with higher frequencies are embryonal tumors (ET), ependymal tumors (EPN) and pilocytic astrocytomas (PA), however, it is often difficult to make a differential diagnosis among them with conventional MRI. The ADC calculated from DWI could be beneficial for diagnostic work up. Method: We acquired DWI at b = 1000 and 4000(s/mm 2 ). The relationship between ADC and the three types of brain tumors was evaluated with Mann-Whitney U test. We also performed simple linear regression analysis to evaluate the relationship between ADC and cellularity, and implemented receiver operating characteristic curve (ROC curve) to test the diagnostic performance among tumors. Results: The highest ADC (b1000/b4000 × 10 −3 mm 2 /s) was observed in PA (1.02−1.91/0.73−1.28), followed by PF-EPN (0.83−1.28/0.60−0.79) and the lowest was ET (0.41−0.75/0.29−0.47). There was significant difference among the groups in both ADC value (b-1000/b-4000: ET vs. PF-EPN p < 0.0001/0.0001, ET vs. PA p < 0.0001/0.0001, PF-EPN vs. PA p < 0.0001/0.0001). ROC analysis revealed that ADC in both b-values showed complete separation between ET and PF-EPN. And it also revealed that ADC at b-4000 could differentiate PF-EPN and PA (96.0%) better than ADC at b-1000 (90.1%). The stronger negative correlation was observed between the ADC and cellularity at b-4000 than at b-1000 (R 2 = 0.7415 vs.0.7070) Conclusions: ADC of ET was significantly lower than the other two groups, and ADC of PA was significantly higher than the other two groups in both b-1000 and b-4000. Our results showed that ADC at b-4000 was more useful than ADC at b-1000 especially for differentiation between PF-EPN and PA.